2019
DOI: 10.25135/rnp.146.19.05.1270
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Gynostemma pentaphyllum Extract in Anti-obesity Therapy

Abstract: In the present study, we investigated a saponin-enriched fraction from Gynostemma pentaphyllum extract (GPE) and isolated gypenoside L (GL), gypenoside LI (GLI), and ginsenoside Rg3 (Rg3). To explore the anti-obesity activities of these compounds, we investigated the effects of GL, GLI, and Rg3 on glucose uptake and activation of AMPK in L6 skeletal muscle cells. GPE, GL, GLI, and Rg3 markedly increased glucose uptake activity and GLUT4 gene expression in L6 myotubes. The enhanced glucose uptake was mediated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
9
0
3

Year Published

2019
2019
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 38 publications
3
9
0
3
Order By: Relevance
“…Total extract or total saponins of G. pentaphyllum have been reported to have diverse effects downstream of AMPK activation [24]. In our previous in vitro study, GPE and gypenoside L, gypenoside LI, and ginsenoside Rg3 were found to activate AMPK [36]. The present study confirmed that GPE treatment activates AMPK in HFD-induced obese C57BL/6N mice.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Total extract or total saponins of G. pentaphyllum have been reported to have diverse effects downstream of AMPK activation [24]. In our previous in vitro study, GPE and gypenoside L, gypenoside LI, and ginsenoside Rg3 were found to activate AMPK [36]. The present study confirmed that GPE treatment activates AMPK in HFD-induced obese C57BL/6N mice.…”
Section: Discussionsupporting
confidence: 82%
“…GPE was prepared at BTC Corporation according to a previously described method [36]. In brief, the leaves of G. pentaphyllum were dried using an electric heat controller (i.e., electric fan).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…G. pentaphyllum was purchased from Hunan Tea Group Co., Ltd (Changsha, Hunan, China), and a voucher specimen (20210301-1) was identified by Professor Zhou Ribao, College of Medicine, Hunan University of Traditional Chinese Medicine. The GPE and GL were prepared at BTC Corporation, according to a previously described method [ 34 ]. In brief, 1 kg of dried G. pentaphyllum leaves were extracted with a hot water (20 L) and 50% EtOH aqueous solution (15 L).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we demonstrated the anti-obesity effect of G. pentaphyllum extract (GPE) and gypenoside L (GL), a saponin isolated from G. pentaphyllum. Both GPE and GL boosted glucose uptake and GLUT4 expression via activation of the AMPK-acetyl-CoA carboxylase (ACC) signaling pathway and promoted mRNA expression of Ppargc1a in skeletal muscle cells [ 34 ]. However, whether GPE and GL regulate the mitochondrial biogenic pathway via PGC-1α expression in C2C12 myotubes remains unclear.…”
Section: Introductionmentioning
confidence: 99%